Clinical Evaluation and Therapeutic Monitoring Value of Serum Tumor Markers in Lung Cancer. Issue 1 (2016) - Wang, Lishui; Wang, Ding; Zheng, Guixi; Yang, Yongmei; Du, Lutao; Dong, Zhaogang; Zhang, Xin; Wang, Chuanxin
Background: Tumor markers CYFRA21-1, CEA, NSE, CA125, pro-GRP and SCC are routinely used for lung cancer. However, there has been no systematic evaluation of these markers in the same cohort. The aim of this study was to evaluate the diagnostic and therapeutic monitoring value of these markers. Methods: The levels of 6 serum tumor markers were measured in 392 patients, including 308 patients with non-small cell lung cancer (NSCLC) and 84 with small cell lung cancer (SCLC), and 116 patients with benign lung diseases and 144 healthy controls. 34 patients were followed up after operation and chemotherapy. Multiple logistic models and receiver operating characteristic (ROC) curves were used to evaluate their diagnostic value. Results: CEA, NSE, CA125 and pro-GRP in SCLC, and CYFRA21-1 as well as CEA in NSCLC, were higher than those in control groups. The level of CEA and CA125 were related to the clinical stages of NSCLC. Pro-GRP was significantly increased in extensive disease (ED) compared with limited disease (LD) in SCLC. CYFRA21-1 was reduced after the third and fifth treatment cycle respectively in patients who undergoing operation and without operation. NSE and pro-GRP were reduced significantly after the second and third treatment cycles, respectively. Conclusions: CEA, NSE, CA125 and pro-GRP could serve as biomarkers for SCLC, and CEA and CYFRA21-1 could serve as biomarkers for NSCLC. Pro-GRP, CA125 and CEA were related to the clinical stages of lung cancer. CYFRA21-1, NSE and pro-GRP could be used for monitoring the effect of chemotherapy.